2021
DOI: 10.1248/cpb.c21-00262
|View full text |Cite
|
Sign up to set email alerts
|

Three New C<sub>19</sub>-Diterpenoid Alkaloids from <i>Aconitum novoluridum</i>

Abstract: Three new aconitine-type C 19 -diterpenoid alkaloid namely novolunines A (1), B (2), and C (3), along with fifteen known diterpenoid alkaloids were isolated from the roots of Aconitum novoluridum, whose phytochemical investigations have never been reported before. The structures of three new alkaloids were established on the basis of spectra data (high-resolution electrospray ionization (HR-ESI)-MS, IR, one dimensional (1D)-and 2D-NMR). Noteworthily, novolunines A (1) and B (2) are two diterpenoid alkaloids be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The former provided 3 novolunines A, B, and C where the structures were established using spectral data analysis. 83 The latter afforded 5 apetalrines A–E based on N -acylated 2-aminobenzoyl esters and also structurally identified following detailed spectral analysis. 84 Ablajan et al reported 5 previously undescribed DA, barpuberudine and barpubesines A–D, and two interesting novel C18 NDA, barpubenines A–B, isolated from the whole plant of A. barbatum var.…”
Section: Analysis Of Ndamentioning
confidence: 99%
“…The former provided 3 novolunines A, B, and C where the structures were established using spectral data analysis. 83 The latter afforded 5 apetalrines A–E based on N -acylated 2-aminobenzoyl esters and also structurally identified following detailed spectral analysis. 84 Ablajan et al reported 5 previously undescribed DA, barpuberudine and barpubesines A–D, and two interesting novel C18 NDA, barpubenines A–B, isolated from the whole plant of A. barbatum var.…”
Section: Analysis Of Ndamentioning
confidence: 99%
“…Compound 3 was obtained as a white amorphous powder with a molecular formula of C37H41N3O7 based on its HR-ESI-MS data. The characteristic NMR data of 3 strongly suggested it to be a C19-diterpenoid alkaloid 8 The NMR data for 3 was similar to those for novolunine C, 3 except that the O-acetamidobenzoate moiety at C-18 of novolunine C was replaced by a 2-(2-methyl-4-oxoquinazolin-3-yl)benzoate moiety in 3, and the methoxy group at H-14 of novolunine C had been replaced by a hydroxyl group in 3, which were further supported by the HMBC correlations. The correlations between H-1 and H-10, H-16 and H-17, H-10 and H-14 in the NOESY spectrum indicated that 1-OMe was α-oriented, 16-OMe was β-oriented, and 14-OH was α-oriented.…”
mentioning
confidence: 68%
“…2 In a previously published article, nineteen diterpenoid alkaloids were isolated from Aconitum novoluridum. 3 However, the diterpenoid alkaloids and their bioactivities have not been studied in detail yet, which prompted us to undertake a systematic study of this plant. Our continued studies on the roots of A. novoluridum have resulted in the isolation of four new diterpenoid alkaloids, which were identified as novolunines D-F (1-3), 8-O-ethylbrevicanine C (4) (Figure 1).…”
mentioning
confidence: 99%
“…Preparation of compounds (6)(7)(8)(9)(10)(11): Compounds 6 and 8-11 were obtained by hydrolyzing the corresponding esters apetaldine F [19], apetaldine J [20], brevicanine [21], talassicumine A [19], and acobretine C [21], respectively. Compound 7 is a naturally occurring C 19 -diterpenoid alkaloids in Aconitum novoluridum [22] 13 C-NMR (CDCl 3 , 100 MHz) data, see ▶ Table 2 [26].…”
Section: Cammaconine (Compoundmentioning
confidence: 99%
“…[22].8-O-methyl cammaconine (compound 8): HR-ESI-MS (m/z 422.2899 [M + H] + ) (calculated for C 24 H 40 NO 5 , 422.2906); 1 H-NMR (CDCl 3 , 400 MHz) δ: 3.10 (1H, dd, J = 10.8 Hz, 6.6 Hz, H-) (calculated for C 25 H 42 NO 5 , 436.3063); 1 H-NMR (CDCl 3 , 400 MHz) δ: 3.09 (1H, dd, J = 10.8 Hz, 6.6 Hz, H-1β), 3.55 (1H, t, J = 4.8 Hz, H-14β), 3.25 (1H, m, H-16α), 3.22, 3.42 (both 1H, ABq, J = 11.2 Hz, H-18), 1.07 (3H, t, J = 7.2 Hz, NCH 2 CH 3 ), 3.13, 3.29, 3.36, 3.37 (each 3H, s, 4 × OCH 3 ) 13. C-NMR (CDCl 3 , 100 MHz) data, see ▶ Table 2[21].…”
mentioning
confidence: 99%